Determinants of Persistence Among Science Teacher-Trainees: - Muwonge, Charles Magoba; Schiefele, Ulrich; Ssenyonga, Joseph; Kibedi, Henry (Journal of Science Teacher Education, 2017)
Grounded in the expectancy-value and hope theories, the present study was conducted to examine the extent to which self-efficacy, task value, and academic hope predict persistence among science teacher-trainees in Uganda. The sample consisted of 278 undergraduate science teacher-trainees selected from a large public university in northern Uganda. Data were collected using several scales from the modified Motivated Strategies for Learning Questionnaire, Academic Hope Scale, and College Persistence Questionnaire and analyzed using structural equation modeling. Task value and academic hope significantly predicted students’ persistence. Academic hope made a greater contribution to students’ persistence compared to task value. The combined effect of task value and academic hope did not make any significant contribution to students’ persistence. The study highlights the need to strengthen students’ hopeful thinking and task value in order to increase their chances of completing their studies. Implications of the study findings for educational practice and for the training of science teacher-trainees are elaborated in the article.
Examining the Role of Self- Efficacy, Task Value, and Academic Hope
Keywords: Academic hope; persistence; science teacher-trainees; self-efficacy; task value